Pelatihan Penggunaan Mesin Sekrap Bagi Mahasiswa di Growth Centre LLDIKTI Wilayah - I - Zulfikar, Achmad Jusuf; Supriatno, Supriatno; Candra, Ifan Aulia; Nurdiana, Nurdiana (CV. IRA PUBLISHING, 2023)
Shaping machine training for students significantly benefits developing technical skills, preparing them for the world of work, and increasing their understanding of manufacturing processes and job safety. A shaping machine is a tool to machine metal surfaces using a reciprocating linear motion. This machine uses a blade moving back and forth to remove a thin metal layer from the work surface and create the desired shape. It is essential to adapt the training method to the needs and characteristics of the participants and provide a safe and conducive environment for learning and practising the use of the shaping machine. Evaluation of technical skills, assessment of theoretical knowledge, and review of the work results of the participants. The experience gained during the training will vary for each participant depending on background, level of expertise, and commitment to learning. The results of this training are expected to increase knowledge and understanding of shaping machines. Participants will learn in-depth about the basic principles of shaping machines, their components, and proper operating techniques.